2016
DOI: 10.1002/2015jc011558
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification and global sensitivity analysis of the Los Alamos sea ice model

Abstract: Changes in the high-latitude climate system have the potential to affect global climate through feedbacks with the atmosphere and connections with midlatitudes. Sea ice and climate models used to understand these changes have uncertainties that need to be characterized and quantified. We present a quantitative way to assess uncertainty in complex computer models, which is a new approach in the analysis of sea ice models. We characterize parametric uncertainty in the Los Alamos sea ice model (CICE) in a standal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 81 publications
(82 reference statements)
4
78
0
Order By: Relevance
“…The model baseline simulation underestimates irradiance below the sea ice. Changing the default value of the sigma coefficient for snow grain (R_snow)—a delta‐Eddington parameter that gives the standard deviation of the snow grain size [ Urrego‐Blanco et al , ]—has a strong effect on simulated light intensity. The best fit was obtained with R_snow = 0.8 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model baseline simulation underestimates irradiance below the sea ice. Changing the default value of the sigma coefficient for snow grain (R_snow)—a delta‐Eddington parameter that gives the standard deviation of the snow grain size [ Urrego‐Blanco et al , ]—has a strong effect on simulated light intensity. The best fit was obtained with R_snow = 0.8 (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…This work does not include a thorough sensitivity analysis, which generally implies changing each parameter at a time, running the model and comparing the results with a reference simulation. However, as already noted by Urrego‐Blanco et al [], such an approach cannot identify interactions among parameters and assumes linearity and additivity. The same authors used a global variance approach with Sobol sequences to efficiently sample the parameter space of the CICE model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Note. Optimized CICE parameters (ksno, rsnw_mlt, R_snw) are based largely on Urrego‐Blanco et al () and Urrego‐Blanco et al (). The E3SMv0‐HiLAT parameter values for ksno and rsnw_mlt are final values; see Table for details of their adjustment during the course of integration.…”
Section: Model Descriptionmentioning
confidence: 99%
“…They ranked the configurations using a variance‐based distance metric, to capture the spatial character of model skill as compared to different observational data sets of sea ice concentration and thickness. Using this distance metric and building on the work of Urrego‐Blanco et al (), who identified parameters for which the simulated sea ice response is more sensitive, the baseline parameter values for the sea ice model component in the coupled E3SMv0‐HiLAT system were taken to be those that had allowed the simulation to best match observations of sea ice concentration (EUMETSAT, NASA Team 1 and 2, and Bootstrap data sets) and sea ice thickness (Unified Sea Ice Thickness Data Record), as documented in Urrego‐Blanco et al ().…”
Section: Model Descriptionmentioning
confidence: 99%